Behavioral effects of triadimefon in zebrafish are associated with alterations of the dopaminergic and serotonergic pathways - Paredes-Zúñiga, Susana; Trost, Nils (Progress in neuro-psychopharmacology & biological psychiatry, 2019)
Triadimefon (TDF) is a triazole fungicide extensively used in agriculture that has been found as a pollutant in numerous water sources. In mammals, it inhibits monoamine uptake through binding to the dopamine transporter, with a mechanism of action similar to cocaine, resulting in higher levels of dopamine at the synapse. Dopamine is a neurotransmitter involved in a broad spectrum of processes such as locomotion, cognition, reward, and mental disorders. In this work we have studied, for the first time, the effects of TDF on behavior of both larval and adult zebrafish and its connection with changes in the dopaminergic and serotonergic systems. We evaluated the acute exposure of 5 dpf larvae to different concentrations of TDF, ranging from 5mg/L to 35mg/L. The lowest concentration does not alter neither locomotor activity nor dopamine levels but produced changes in the expression of two genes, tyrosine hydroxylase 1 (th1) and dopamine transporter (dat). Besides, it induced a reduction in extracellular serotonin and had an anxiolytic-like effect, supported by a decrease in cortisol production. On the other hand, a high concentration of TDF produced a dose-dependent reduction in locomotion, which was reversed or enhanced by D1 (SCH-23390) or D2 (Haloperidol) dopamine receptor antagonists, respectively. Using in vivo electrochemistry, we show that these changes could be associated with higher levels of dopamine in the brain. Thus, in adult zebrafish, though not in larvae, TDF exposure increases locomotor activity, anxiety and aggressiveness, which coincides with the behaviors observed in mammals.
Gesehen am 05.06.2019
Available online: 26 December 2018